2021
DOI: 10.1093/mnras/stab998
|View full text |Cite
|
Sign up to set email alerts
|

The AGNIFS survey: distribution and excitation of the hot molecular and ionized gas in the inner kpc of nearby AGN hosts

Abstract: We use the Gemini NIFS instrument to map the H2 2.1218 μm and Brγ flux distributions in the inner 0.04–2 kpc of a sample of 36 nearby active galaxies (0.001 ≲ z ≲ 0.056) at spatial resolutions from 4 to 250 pc. We find extended emission in 34 galaxies. In ∼55 per cent of them, the emission in both lines is most extended along the galaxy major axis, while in the other 45 per cent the extent follows a distinct orientation. The emission of H2 is less concentrated than that of Brγ, presenting a radius that contain… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(44 citation statements)
references
References 117 publications
3
40
0
1
Order By: Relevance
“…As reported previously, radio and nearinfrared (e.g. Rodríguez-Ardila et al 2004;Storchi-Bergmann et al 2009;Riffel et al 2010Riffel et al , 2021cMezcua et al 2015;Schönell et al 2017;Bianchin et al 2022, among others) observations have shown that AGNs harbor a neutral and warm (1000-3000 K) molecular gas reservoir. Therefore, a substantial proportion of neutral helium is expected in Seyfert nuclei.…”
Section: Ionization Correction Factorsupporting
confidence: 51%
See 1 more Smart Citation
“…As reported previously, radio and nearinfrared (e.g. Rodríguez-Ardila et al 2004;Storchi-Bergmann et al 2009;Riffel et al 2010Riffel et al , 2021cMezcua et al 2015;Schönell et al 2017;Bianchin et al 2022, among others) observations have shown that AGNs harbor a neutral and warm (1000-3000 K) molecular gas reservoir. Therefore, a substantial proportion of neutral helium is expected in Seyfert nuclei.…”
Section: Ionization Correction Factorsupporting
confidence: 51%
“…In fact, Méndez-Delgado et al (2022) found that only 9/42 Galactic H regions have negligible contributions of 𝑦 0 (see also Delgado-Inglada et al 2014). Since AGNs present a large amount of molecular gas (e.g., Rodríguez-Ardila et al 2004;Davies et al 2005;Rodríguez-Ardila et al 2005;Mazzalay et al 2013;Riffel et al 2013Riffel et al , 2018Riffel et al , 2021cRamakrishnan et al 2019;Riffel et al 2019;Jarvis et al 2020;Alonso-Herrero et al 2020) and have similar ionization parameter (𝑈) other than SFs (Pérez-Montero et al 2019), a higher abundance of neutral and molecular gas are expected in AGNs as compared to H regions, which favors the presence of larger contribution of 𝑦 0 in the total helium abundance. In fact, radio observations have shown the existence of a gas neutral reservoir in the central parts of galaxies containing AGNs (e.g.…”
Section: Helium Abundancementioning
confidence: 98%
“…This value is much larger than the nuclear gas masses of between 4 and 74 M measured by Mazzalay et al (2013) for a sample of six nearby low-luminosity AGN using data from VLT/SINFONI. A larger average gas mass, of 850 M , was reported by Riffel et al (2021) for a larger sample of nearby Seyfert 2 galaxies observed with Gemini/NIFS as part of the AGNIFS survey. Finally, our mass is similar to those measured for other QSO2s in the QSOFEED sample.…”
Section: The Warm Molecular Gasmentioning
confidence: 71%
“…Higher resolution CO(2-1) (beam size of 0.214 × 0.161 arcsec 2 ) ALMA observations unravelled the structure of the ring: several star-forming clumps associated with star formation events (Alonso-Herrero et al 2019 ). The presence of a ring of star-forming regions is also supported by the low H 2 /Br γ ratios (Sch önell et al 2019 ;Riffel et al 2021c ), higher Br γ equi v alent width (Rif fel et al 2021c ), lo w gas ( ∼50 km s −1 -Fig. 4 ), and stellar velocity dispersion (Barbosa et al 2006 ;Riffel et al 2017 ) values.…”
Section: B4 Ngc 3227mentioning
confidence: 87%